Hepatitis C virus infection and diabetes: A complex bidirectional relationship - Ciardullo, Stefano; Mantovani, Alessandro; Ciaccio, Antonio; Carbone, Marco; Invernizzi, Pietro; Perseghin, Gianluca (Diabetes research and clinical practice, 2022)
Chronic hepatitis C (CHC) and diabetes represent two severe chronic conditions responsible for a considerable number of deaths worldwide. They have a complex, bidirectional relationship. On the one hand, several cohort studies have shown that chronic HCV infection increases both the risk of developing diabetes in non-diabetic subjects (by inducing insulin resistance and promoting β-cell dysfunction) as well as the risk of developing macro and microvascular complications in patients with known diabetes; on the other hand, diabetes is an independent risk factor for liver-related events among patients with CHC, including a higher incidence of hepatocellular carcinoma, liver-related death and transplantation. Importantly, sustained virological response, which can be obtained in the vast majority of patients with the use of direct antiviral agents, does not only lead to a lower rate of liver-related outcomes, but also to improvements of glycemic control and reduction in the rate of complications among patients with diabetes. The aim of this review is to summarize available clinical evidence on the association among CHC, diabetes and related clinical outcomes. We will also briefly discuss the biological mechanisms underpinning the association between CHC and diabetes, as well as the implications this relationship should have on everyday clinical practice.